2010
DOI: 10.1002/cncr.25652
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of Notch pathway activating compounds through a novel high‐throughput screening method

Abstract: BACKGROUND: Carcinoids are neuroendocrine (NE) tumors with limited treatment options. Notch activation has been shown to suppress growth and hormone production in carcinoid cells. METHODS: The purpose of this study was to provide a process for identifying Notch activating compounds via high‐throughput screening (HTS) and to validate the effects of the strongest hit from the 7264 compounds analyzed: resveratrol (RESV). RESULTS: Treatment of carcinoid cells with RESV resulted in up‐regulation of the Notch signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 56 publications
1
47
0
Order By: Relevance
“…S5A). Consistent with their previously described roles (14,18,19), we found that VEGFA, WNT3A, and resveratrol [RESV, a NOTCH agonist (20)] promoted arterial specification (SI Appendix, Fig. S5 B-F).…”
Section: Significancesupporting
confidence: 90%
“…S5A). Consistent with their previously described roles (14,18,19), we found that VEGFA, WNT3A, and resveratrol [RESV, a NOTCH agonist (20)] promoted arterial specification (SI Appendix, Fig. S5 B-F).…”
Section: Significancesupporting
confidence: 90%
“…Thus, we sought to identify a small molecule which induces Notch3 in MTC cells. We had previously developed a high throughput screen for Notch activating compounds (34). Utilizing this system, we identified a synthetic compound, AB3, which appeared to have this property.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that Notch effectors are downregulated in G9a-mutant labyrinth endothelium and in the chorionic villi of human placentae affected by IUGR opens the possibility that pharmacological activation of the Notch pathway in the placenta might be a potential strategy to prevent or treat abnormal maturation of the placental vasculature. Valproic acid, which is used to control epileptic seizures and psychiatric disorders, was found to activate the Notch pathway resulting in increased activity of Rbpj (Pinchot et al, 2011). The use of valproic acid during pregnancy has limitations as it can promote a higher risk of neural tube closure defects in babies when administered during the first trimester of pregnancy (Jentink et al, 2010).…”
Section: Discussionmentioning
confidence: 99%